Meningkatkan Kemampuan Menulis Karangan Narasi melalui Pendekatan Kontekstual dengan Inspirator Lingkungan Sekolah Siswa Kelas VIII-1 SMP Negeri 1 Brang Rea - Saerni (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
This study aims to find out and reveal that the application of a contextual approach with school environment inspiration can improve the ability to write narrative essays for class VIII-1 students of SMP Negeri 1 Brang Rea, and find out and find contextual learning steps to improve narrative essay writing skills. The subjects of this study were students of class VIII-1 SMP Negeri 1 Brang Rea. This research uses a classroom action research design and was carried out in the 2018/2019 academic year, carried out in three cycles, in which the three cycles discussed one linguistic aspect, namely